CONVERSATIONAL STYLE USED BY NAJWA SHIHAB AND THE MALLARANGENGS ON MATA NAJWA TALK SHOW PROGRAM JURUS MALLARANGENG EPISODE - TANDUNGAN, ELYSA RATNA SARI DEWI (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Conversational Style, Mata Najwa, Najwa Shihab, Andi Mallarangeng, Rizal Mallarangeng. This study investigates the conversational style used by Najwa Shihab and The Mallarangengs on Mata Najwa talk show program Jurus Mallarangeng episode. Mata Najwa is one of Metro TV talk show programs hosted by a senior journalist, Najwa Shihab. In conducting the research, the writer tries to analyze the conversational style used by Najwa Shihab, Andi Mallarangeng who is the Former Minister of Youth and Sports Affairs as well as the suspect of Hambalang corruption case, and Rizal Mallarangeng who is The Mallarangengs Spokesman.The problem to be solved the study is what is the conversational style used by Najwa Shihab and the Mallarangengs on Mata Najwa Talk Show Program Jurus Mallarangeng Episode. The main theory used in this study is Tannen’s (2005), supported by Yule’s (1996) theory.This study used qualitative approach since the writer tried to analyze the utterances of Najwa Shihab and The Mallarangengs. The data of the study were Najwa Shihab’s and The Mallarangengs’s utterances containing conversational style in Mata Najwa talk show Jurus Mallarangeng episode.It was found out that Najwa Shihab and The Mallarangengs often used high involvement style than high considerateness Style almost in every segment. It is proven by the usage of each feature of high involvement style such as topic, pacing and expressive paralinguistic proposed by Tannen (2005), which are often use than high considerateness style such as slow turn taking and slow rate of speech proposed by Yule (1996).To sum up, Najwa Shihab often uses high involvement style to criticize Hambalang corruption case, which involve The Mallarangengs. Further, Andi Mallarangeng and Rizal Mallarangeng use high involvement style to clarify the truth about hambalang corruption case.The writer suggests English Department students discussed about conversational style. She also suggests the next researchers conduct a study about conversational style using different object, such as Oprah Winfrey talk show.